The Association Between Sustained Poor Quality of Life and Future Opioid Use in Inflammatory Bowel Disease. Issue 7 (31st May 2018) - Anderson, Alyce; Click, Benjamin; Ramos-Rivers, Claudia; Koutroubakis, Ioannis E; Hashash, Jana G; Dunn, Michael A; Schwartz, Marc; Swoger, Jason; Barrie, Arthur; Regueiro, Miguel; Binion, David G
Abstract: Background: Inflammatory bowel disease (IBD) is associated with poor quality of life and disability. The short inflammatory bowel disease questionnaire (SIBDQ) is validated to determine patients quality of life at single time points, or improvement over time. Few studies have evaluated if sustained poor quality of life is associated with future healthcare utilization patterns. Methods: We analyzed patients from a prospective IBD natural history registry with 4 consecutive years of follow-up. SIBDQ was measured at outpatient visits. Healthcare utilization data were temporally organized into a 2-year observation period, and 2-year follow-up period. Mean SIBDQ score <50 during the first 2 years was categorized as having "poor quality of life". Primary outcomes of interest were measures of unplanned healthcare utilization and opioid use. Results: From a total of 447 participants (56.1% female, 66.1% Crohn's disease, 34.9% ulcerative colitis), 215 (48.1%) were classified as having poor quality of life. Poor quality of life was significantly associated with Crohn's disease ( P < 0.01), history of IBD related surgery, and tobacco use (all P < 0.01). In the follow-up period, the same patients with poor quality of life were more likely to have abnormal biomarkers of inflammation, more telephone calls and office visits, experience unplanned care, and be exposed to opiates (all P < 0.05). After multivariable analysis, poor quality of life remained an independent predictor of future opiate use (odds ratio: 2.2, P = 0.003) and decreased time to first opiate prescription (hazard ratio: 1.67, P = 0.019) in the follow-up period. Conclusions: IBD patients with sustained poor quality of life are at an increased risk of opiate use and decreased time to opiate exposure. Routine measurement of quality of life in the outpatient setting may provide insight into those at risk for narcotic use and healthcare utilization.